(untitled) (Pakistan Journal of Science, 2022)
Multi-storied frame structures have always been in the lime-light as far as research and theoretical development is concerned. The behavior of lateral forces on the structures is a specific area on which considerable research has been done over the last few decades. Several experiences of the last century have brought the attention of the engineers to such forces which, at times, were significant enough to change the design criteria. In Pakistan, considerations for such lateral forces had been made compulsory by the building control authorities across the country, and the same were welcomed, after the catastrophic disaster of October 2005. However, the developmental research in the field is still underway like in rest of the world. Most of the structural designers in Pakistan depend on Computer Aided Design software for analysis of lateral forces; however, significance of classical methods cannot be over-ruled. In this study, an attempt was made by studying the comparison between the design results of a multi-storied moment resisting frame structure in Karachi using the D-value method and ETABS software. There are several parameters on which the comparison could be based, but as the designers are mostly concerned about the design moments, the comparison is based upon the difference between the moments caused on respective joints by the lateral forces only. D-value method is not only a straightforward method but also may be considered to be the nearest compatible method to the finite element method (ETABS), for the analysis of lateral forces on super-structures, as its results showed a variation of only 20% with that of the results from ETABS. It is recommended for preferable use D-value method upon other methods of analysis when it comes to the scrutiny or verification of moments from the CAD software however, the difference between the comparative results may vary for type of structures other than the moment resisting frame structures.